Navigated MRI-guided liver biopsies in a closed-bore scanner: experience in 52 patients - Moche, Michael; Heinig, Susann; Garnov, Nikita; Fuchs, Jochen; Petersen, Tim-Ole; Seider, Daniel; Brandmaier, Philipp; Kahn, Thomas; Busse, Harald (European Radiology, 2016)
To evaluate clinical effectiveness and diagnostic efficiency of a navigation device for MR-guided biopsies of focal liver lesions in a closed-bore scanner.